Training on improving food products through the development of aloe vera-based products in Argomulyo Village, Sedayu, Bantul - Anton Yudhana; Nur'Aini Purnamaningsih; Wiwiek Afifah; Novi Febrianti (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The objective of this community service activity to increase the capacity of the community of Argomulyo Village, Sedayu, Bantul, to develop aloe vera-based food products, specifically aloe vera nata. The main problems faced by the community include the suboptimal utilization of aloe vera, the lack of processing technology, and a lack of understanding of good food production standards. The training was conducted through outreach, demonstrations on making aloe vera nata, and mentoring on sustainable production. Through these activities, participants gained knowledge about the nutritional content and economic potential of aloe vera, understood the principles of fermentation, and were able to produce aloe vera nata. Evaluation results showed an increase in participants' knowledge and skills in making aloe vera nata. This activity is expected to be the first step in strengthening the community's economy through innovative aloe vera products